2019
DOI: 10.1097/psy.0000000000000770
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Resilience and Vulnerability as Mediators Between Adverse Life Events and Fatigue, Motor Dysfunction, and Paresthesia in Multiple Sclerosis

Abstract: Objective Adverse life events have been associated with exacerbating multiple sclerosis (MS) symptoms, but results have been variable, raising the question on the role of other psychological factors. This study examined the role of psychological resilience and vulnerability as mediators between adverse life events on MS symptoms. Methods Participants with MS (N = 1239) were aged 18 to 81 years (mean [SD] = 45.6 [10.4] years), and 84.5% were female. MS s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…Psychological vulnerability refers to core beliefs and thoughts that people have that can interfere with their daily life and negatively affect their mood. Previous studies showed psychological vulnerability mediating the relationship between adverse life events and MS symptoms ( 38 ). Interestingly, the results of this study showed that people with SPMS showed greater negative core beliefs compared to people with PPMS, which may indicate that the secondary progressive course of disease may make these core beliefs more salient.…”
Section: Discussionmentioning
confidence: 97%
“…Psychological vulnerability refers to core beliefs and thoughts that people have that can interfere with their daily life and negatively affect their mood. Previous studies showed psychological vulnerability mediating the relationship between adverse life events and MS symptoms ( 38 ). Interestingly, the results of this study showed that people with SPMS showed greater negative core beliefs compared to people with PPMS, which may indicate that the secondary progressive course of disease may make these core beliefs more salient.…”
Section: Discussionmentioning
confidence: 97%
“…Higher psychological resilience has previously been identified as a non-disease-specific factor associated with better physical function in pwMS. ( Klineova et al, 2020 , Swanepoel et al, 2020 ) For example, a recent longitudinal study examining the risk and protective factors for cognitive decline [Reserve against disability in early MS (RADIEMS)] showed that pwMS with greater CD-RISC scores had better objective functional outcomes, including both motor and cognitive indices. ( Klineova et al, 2020 ) When compared to more vulnerable counterparts, pwMS with greater resilience also exhibit less neurological symptoms (paresthesia, motor dysfunction, fatigue) within the 60 days after an adverse life event.…”
Section: Discussionmentioning
confidence: 99%
“…( Klineova et al, 2020 ) When compared to more vulnerable counterparts, pwMS with greater resilience also exhibit less neurological symptoms (paresthesia, motor dysfunction, fatigue) within the 60 days after an adverse life event. ( Swanepoel et al, 2020 ) Therefore, resilience-targeted interventions may provide benefits to both mental and physical outcomes. ( Pakenham et al, 2018 ) PwMS with greater social support ( e.g., belonging to patient community) have significantly greater resilience and sense of coherence, and use more suitable coping strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, more short-term changes in fatigue are linked foremost to temporally constrained events such as acute viral infections (Carrat et al, 2008), or environmental factors such as temporary stress (Doerr et al, 2015). As previous research has shown, the effects of acute events on behavioral regulation can differ depending on whether or not they are accompanied by more or less severe baseline conditions (Haeffel et al, 2008; Swanepoel et al, 2020), similar to vulnerability models of diseases (Ingram & Luxton, 2005).…”
Section: Introductionmentioning
confidence: 95%